A membrane disdrometer based on membrane vibration. (14th October 2015) - Lu, Junhui; Yang, Zhihong; Wang, Jianqiang
Abstract: Raindrop sizes were indirectly determined through the distinctive vibrations and sounds that occur when raindrops of different sizes impact on a membrane. The relationships between diameter, raindrop kinetic momentum, membrane deflection, and impact force were analyzed. Membrane deflection and vibration models were created, and the optimum membrane diameter and thickness were identified. A prototype membrane disdrometer was developed on the basis of these findings. The relationship between raindrop size and membrane vibration sound pressure was determined experimentally. The fundamental parameter of raindrop size recognition was used. The test results indicate that raindrops 0.4–2.0 mm in diameter can be detected by the proposed membrane disdrometer, and 50 raindrops per second in a zone area of 28.3 cm 2 can be detected in natural rain.